High School Students’ Motivation Towards Physics Learning During Covid-19 Outbreak - Sukmawati, Sukmawati; Qadar, Riskan; Sulaeman, Nurul Fitriah (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
Learning activities during the covid-19 pandemic have adapted by utilizing e-learning platforms, and this condition encourages the need to help students, especially by knowing their many motivations. Thus, this study aims, 1) To determine the level of student learning motivation in general and by gender 2) To determine the percentage of the ARCS aspect of each school on the level of learning motivation in general and by gender, 3) To determine the percentage of the ARCS aspect as a whole to the level of motivation to learn in general and by gender after participating in Physics learning boldly. The research sample was 275 students of class X MIPA from 8 public schools in Balikpapan. Data collection using questionnaires and interview techniques. The results showed that the general level of motivation was moderate with a percentage of 49%, while the value based on the proportion of gender for male students was 37% and the percentage for students was 63%. , 64.23% for Relevance, 68.19% for Confidence, and 71.95% for Satisfaction, while the proportion value based on gender in Attention is 67.53% for male, 67.80% for female; Male relevance 65.07%, female 63.78%; Confidence of men 69.41%, women 67.55%; and male satisfaction 72.37%, female 71.74%. Basically, this study aims to determine the level of motivation to learn physics and the aspects that affect that motivation; the higher the motivation, the greater the learning success. This study shows that high school students' motivation to learn physics based on the ARCS learning model is in the medium category. By knowing the level of learning motivation from several aspects that have been explored, we can increase students' motivation to learn to the maximum in the next lesson.